THE EVA IN THE EVALUATION OF INVESTMENT ALTERNATIVES - Mavila Hinojoza, Daniel (2006)
EVA (Economic Value Added) is a specific indicator of residual income that many companies used nowadays to measure its performance. Its fundament is that the supreme objective of the directives of the organization is to create value, and for that it was conceived as the tool able to measure if that goal is effectively fulfilled. In this article, we show that through MVA (Market Value Added) we will update EVAs previously calculated, allowing to evaluate an alternative of inversion as an alternative method to VAN.